Perinatal Outcome in Explained and Unexplained Polyhydramnios - Maliha Sadaf, Sobia Nawaz Malik ,Jehan Ara, Sadaf Tufail, Shagufta Saeed Sial (Journal of Rawalpindi Medical College, 2013)
Background: To compare the perinatal outcome between explained and unexplained (idiopathic) polyhydramnios. Methods: In this descriptive study, 50 women with singleton pregnancies with idiopathic polyhydramnios, delivered in a period of one year, were compared with 45 pregnant women with known causes of polyhydramnios. Outcome measures studied were preterm delivery (<37 weeks gestation), low birth weight (<2.5 kg), macrosomia (>4.0 kg), malpresentations, APGAR score at 5 minutes <7, rate of caesarean section, neonatal hospitalization, congenital anomalies and perinatal death. Results: Incidence of polyhydramnios was found to be 1.36%. In 52.63% of cases no cause of polyhydramnios was found, while 47.37% of cases were found to have underlying causes of polyhydramnios. There was a statistically significant increased incidence of preterm delivery (31%, p-value < 0.05), caesarean section (44.4%, p-value<0.05), NICU admission (33%, p-value < 0.05), congenital anomalies (22%, p-Value < 0.05) and perinatal death (20%, p-value < 0.05) in explained polyhydramnios group as compared to unexplained polyhydramnios group. There was also an increased incidence of malpresentations (24.4%) and low APGAR score (33%) in explained polyhydramnios group. Conclusion: Antenatal diagnosis of polyhydramnios requires careful search for associated underlying maternal and fetal conditions. Idiopathic Polyhydramnios is not associated with adverse perinatal outcome